Polycomb complexes redundantly maintain epidermal stem cell identity during development - Cohen, Idan; Bar, Carmit; Liu, Hequn; Valdes, Victor J.; Zhao, Dejian; Galbo, Phillip M.; Silva, Jose M.; Koseki, Haruhiko; Zheng, Deyou; Ezhkova, Elena (Genes & development, 2021)
Polycomb repressive complex 1 (PRC1) and PRC2 are critical epigenetic developmental regulators. PRC1 and PRC2 largely overlap in their genomic binding and cooperate to establish repressive chromatin domains demarcated by H2AK119ub and H3K27me3. However, the functional contribution of each complex to gene repression has been a subject of debate, and understanding of its physiological significance requires further studies. Here, using the developing murine epidermis as a paradigm, we uncovered a previously unappreciated functional redundancy between Polycomb complexes. Coablation of PRC1 and PRC2 in embryonic epidermal progenitors resulted in severe defects in epidermal stratification, a phenotype not observed in the single PRC1-null or PRC2-null epidermis. Molecular dissection indicated a loss of epidermal identity that was coupled to a strong derepression of nonlineage transcription factors, otherwise repressed by either PRC1 or PRC2 in the absence of its counterpart. Ectopic expression of subsets of PRC1/2-repressed nonepidermal transcription factors in wild-type epidermal stem cells was sufficient to suppress epidermal identity genes, highlighting the importance of functional redundancy between PRC1 and PRC2. Altogether, our studies show how PRC1 and PRC2 function as two independent counterparts, thereby providing a repressive safety net that protects and preserves lineage identity.